Single production of fourth-family t′ quarks at the CERN Large Hadron electron Collider - Cakir, O.; Senol, A.; Tasci, A. T. (IOP Publishing, 2009)
We study the electroweak single production of fourth-family t' quarks via the process ep?t'? at the Large Hadron electron Collider (LHeC). We calculate the background and signal cross-sections for the mass range 300?800?GeV. It is shown that the LHeC can discover a single t' quark up to the mass of 750?GeV for the optimized mixing parameters.
Keywords: 7. Clean energy